141: Self-Evaluation of Procedural Skill Competencies By Neonatal Perinatal Medicine Trainees in Canada. Issue 6 (1st June 2014) - Fiedrich, E; Amin, H; White, J; Joynt, C
Abstract: BACKGROUND: Procedural competence is defined as "the ability to perform a procedure independently, without supervision, with a high likelihood of successful completion" (Gaies MG et al. Pediatrics. 2007;120(4):715–22). The Royal College of Physicians and Surgeons of Canada has outlined 19 procedural skills for Neonatal-Perinatal Medicine (NPM) trainees to demonstrate competence by the end of a two-year program. It is unclear how Canadian NPM training programs prepare their residents to acquire these procedural skills. There is no formal way to evaluate which competencies require increased training or exposure. OBJECTIVES: To examine the self-reported attitudes and procedural skill competencies of Neonatal Perinatal Medicine trainees across Canada for 19 procedural skills listed by the Royal College for NPM training. DESIGN/METHODS: A cross-sectional confidential electronic survey was sent to first and second year NPM trainees in 13 Canadian NPM programs (2012–2013). A five-point Likert scale was used to rate perceived importance (1 = not important to 5 = very important) and competence (1 = not competent to 5 = neonatologist) of each skill before and during their NPM training. Demographic and training data was collected. Two-tailed paired t tests (P<0.05) were used to analyze pre versus current training "competence" for each skill. Only anonymous aggregate data was reported. RESULTS: A total of 47 trainees (68%) completed the survey of which 36 consenting respondents with >6 months Canadian NPM training were analyzed. Only 25% of trainees were FRCPC exam eligible (CMG) (25%), with majority of respondents 12 to 24 months (47.3%) into their training. There were larger changes in pre versus current training perceived competencies in CMG compared to international medical graduates. Most CMG's procedural skills reached competence and improved by >1 during training, with the exception of suprapubic (mean difference 0.55), urinary catheterization (0.67), pericardiocentesis (0.45), and paracentesis (1.00). Pericardiocentesis did not meet competence (1.9/5) despite type and duration of training. Skills performed frequently in NICU (compared to pediatric residencies): umbilical lines (1.3), intubation (1.2), chest tubes (1.7), PICC lines (1.7), and arterial lines (1.5) had a high level of change and competence. Despite training, some NICU procedures rated poorly (x/5) in self-rated competence including paracentesis (2.4), PICC line insertion (3.1), suprapubic tap (2.2) and exchange transfusion (3.1). CONCLUSIONS: Observed skills most frequently done by trainees have the greatest change in competence during training for CMG in NPM. Some necessary procedural skills may require changes to instruction methods and these results could help guide curricular improvement.